2018
DOI: 10.1093/cid/ciy532
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Human Immunodeficiency Virus in Influenza- and Respiratory Syncytial Virus–associated Hospitalizations in South African Children, 2011–2016

Abstract: Influenza- and RSV-associated hospitalization are common among South African infants. HIV infection, and HIV exposure in infants, increase risk of influenza- and RSV-associated hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 27 publications
8
27
0
Order By: Relevance
“…Conversely, young infants infected with influenza had a significantly higher rate of fever than children with RSV infection. These results are consistent with previous reports on the RSV and influenza clinical features in young children [8,9]. We also found that a radiologically confirmed pneumonia was more frequent in RSV infection than in influenza infection, which is in line with other publications [7,8].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Conversely, young infants infected with influenza had a significantly higher rate of fever than children with RSV infection. These results are consistent with previous reports on the RSV and influenza clinical features in young children [8,9]. We also found that a radiologically confirmed pneumonia was more frequent in RSV infection than in influenza infection, which is in line with other publications [7,8].…”
Section: Discussionsupporting
confidence: 94%
“…We found the highest rate of RSV among infants aged 3-5 months with RSV detection in nearly three over four patients (73.5%) followed by infants < 3 months (53.7%). Similar to our results, other reports found that infants aged 3-5 months had the highest proportion of RSV detection [3,10], while the highest RSV frequency in the South African study was among infants < 3 months [9].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…[10] HEU infants have an increased risk of hospitalisation compared to HIV-unexposed infants and an increased risk of in-hospital death, predominantly in the first 6 months of life. [11,12] Increased risk of hospitalisation in HEU infants has also been found for specific pathogens such as pneumococcus, respiratory syncytial virus (RSV) and influenza virus. [10,11,13] Additional risk factors for severe pneumonia include infancy (particularly those <4 months), premature birth, incomplete immunisation, maternal smoking or household tobacco smoke exposure, indoor air pollution, low birthweight, malnutrition, lack of exclusive breastfeeding and overcrowding.…”
Section: Epidemiologymentioning
confidence: 99%
“…In addition, it can often be the case that RTIs exist simultaneously with underlying co-morbidities, such as tropical diseases in Low-and Middle-Income Countries, 11,12 cancer and HIV, 12,13 or sudden outbreaks of epidemics/pandemics, especially of respiratory nature like the SARS-CoV-2. 14,15 In such occasions, the epidemiological landscape becomes even more complicated, requiring accurate diagnosis of the RTI-causative pathogen for proper management of patients with comorbidities.…”
Section: Introductionmentioning
confidence: 99%